Systematic review of functional outcome and quality of life after total pancreatectomy. Issue 13 (10th September 2019) - Scholten, L; Stoop, T F; Del Chiaro, M; Busch, O R; Eijck, C; Molenaar, I Q; Vries, J H; Besselink, M G
Abstract: Background: Surgeons have traditionally been reluctant to perform total pancreatectomy because of concerns for brittle diabetes and poor quality of life (QoL). Several recent studies have suggested that outcomes following total pancreatectomy have improved, but a systematic review is lacking. Methods: A systematic review was undertaken of studies reporting on outcomes after total pancreatectomy for all indications, except chronic pancreatitis. PubMed, EMBASE (Ovid), and Cochrane Library were searched (2005–2018). Endpoints included functional outcome and QoL. Results: A total of 21 studies, including 1536 patients, fulfilled the eligibility criteria. During a median follow-up of 20·8 (range 1·5–96·0) months, 18·6 per cent (45 of 242 patients) were readmitted for endocrine-related morbidity, with associated mortality in 1·6 per cent (6 of 365 patients). No diabetes-related mortality was reported in studies including only patients treated after 2005. Symptoms related to exocrine insufficiency were reported by 43·5 per cent (143 of 329 patients) during a median follow-up of 15·9 (1·5–96·0) months. Overall QoL, reported by 102 patients with a median follow-up of 28·6 (6·0–66·0) months, using the EORTC QLQ-C30 questionnaire, showed a moderately reduced summary score of 76 per cent, compared with a general population score of 86 per cent ( P = 0·004). Conclusion: Overall QoL after total pancreatectomy is affected adversely, in particular by the considerable impact of diarrhoea that requires better treatment. There is also room for improvement in the management of diabetes after total pancreatectomy, particularly with regards to prevention of diabetes-related morbidity. Graphical Abstract: Report of a systematic review of outcomes following total pancreatectomy. Diabetes and diarrhea should be improved